2011
DOI: 10.1080/10934529.2011.602937
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects and oxidative stress response of six PBDE metabolites on human L02 cells

Abstract: In the present study, the cytotoxic effects and toxicological mechanism of six polybrominated diphenyl ethers (PBDEs) metabolites (3-OH-BDE47, 3-MeO-BDE47, 5-OH-BDE47, 5-MeO-BDE47, 6-OH-BDE85 and 6-MeO-BDE85) on L02 cells were explored by investigating the cell viability, apoptosis, lactic dehydrogenase (LDH) leakage, and oxidative stress response. The results showed that these metabolites could inhibit cell proliferation and induce apoptosis, among which 6-OH-BDE85 had the highest efficiency. LDH leakage test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Recently, experimental data using animal models strongly suggested the occurrence of PBDE immunotoxicity, manifested as altered splenic lymphocyte populations, increased susceptibility to infections, and the release of pro-inflammatory cytokines (Zhong et al, 2011;Pellacani et al, 2012;Bondy et al, 2013). However, the data on PBDE immunotoxicity are still limited, and the mechanism(s) remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, experimental data using animal models strongly suggested the occurrence of PBDE immunotoxicity, manifested as altered splenic lymphocyte populations, increased susceptibility to infections, and the release of pro-inflammatory cytokines (Zhong et al, 2011;Pellacani et al, 2012;Bondy et al, 2013). However, the data on PBDE immunotoxicity are still limited, and the mechanism(s) remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The data showed that the reduction of GSH occurred in parallel with the over-production of ROS, in response to BDE-47 and BDE-209 exposure. In vitro, at various concentrations, PBDE-induced oxidative stress was also commonly found in many cell lines, including gonadal cells and germ cells (Jin et 2012), liver cells (Zhong et al, 2011), and immune cells (Yan et al, 2011), causing global gene disturbance and DNA damage. In vivo, oxidative stress was previously demonstrated as a mechanism of PBDE toxicity in earthworms (Eisenia fetida) (Xie et al, 2011) and CD-1 mice (Tseng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…PBDE-induced oxidative stress has also been observed in non-nervous tissue cell types, such as human fetal liver hematopoietic cells (Shao et al 2008), human hepatoma cells HepG2 (Hu et al 2007; 2009), Jurkat T cells (Yan et al 2011), and human umbilical vein endothelial cells (Kawashiro et al 2009). Certain hydroxylated PBDEs have also been shown to induce oxidative stress in human liver L02 cells (Zhong et al 2011). …”
Section: Potential Mechanisms Of Pbde Developmental Neurotoxicitymentioning
confidence: 99%
“…In addition, BDE-47 is one of five main PBDE congeners Some in vitro studies have revealed that BDE-47 could cause toxic effects, such as developmental neurotoxicity, hepatotoxicity, reproduction toxicity, immunotoxicity and endocrine disruption (Lema et al, 2008;Song et al, 2009;Kodavanti et al, 2010;An et al, 2011;Erratico et al, 2011;Zhong et al, 2011;Chen et al, 2012). Apoptosis is a form of self-regulated cell death and a major manifestation of cytotoxicity of contaminants (Kerr et al, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…In traditional toxicological studies, one or several biomarkers are usually chosen to assess the cytotoxicity of BDE-47 such as apoptosis and ROS production to test for oxidative stress or specific expressed proteins and genes to test for certain toxicities (Crump et al, 2008;Zhong et al, 2011;Wang et al, 2012). However, a single biomarker only indicates a certain toxic effect, which usually lacks a global view on cytotoxicity of BED-47.…”
Section: Introductionmentioning
confidence: 99%